Hierarchical spheres constructed by defect-rich MoS2/carbon nanosheets for efficient electrocatalytic hydrogen evolution. (April 2016) - Yang, Linjing; Zhou, Weijia; Lu, Jia; Hou, Dongman; Ke, Yunting; Li, Guoqiang; Tang, Zhenghua; Kang, Xiongwu; Chen, Shaowei
Abstract: Highly active and stable MoS2 /carbon hierarchical spheres with abundant active edge sites were fabricated by a simple micro-emulsion procedure where PVP was used as the carbon source, and carbon disulfide as the sulfur source and oil phase in micro-emulsion to control the morphology of MoS2 . Hierarchical spheres of MoS2 /carbon with a diameter of ca. 500 nm were obtained and characterized by scanning and transmission electron microscopic measurements. With a high electrochemically accessible surface area and defect-rich MoS2 nanosheets, the MoS2 /carbon hierarchical spheres exhibited an excellent electrocatalytic activity for hydrogen evolution reaction with a low onset potential of −103 mV (vs. RHE), small Tafel of 56.1 mV dec −1, as well as extraordinary catalytic stability. The results were accounted for by the "inverted molybdenum reaction" that served as a novel way of regulating Mo catalytic sites of MoS2 electrocatalysts. Graphical abstract: Highlights: Defect-rich MoS2 /carbon hierarchical spheres with more active sites were prepared by simple micro-emulsion method. The C–MoS2 hierarchical spheres exhibited a low onset potential of −103 mV (vs. RHE) with a Tafel slope of 56.1 mV dec −1 . The "inverted molybdenum reaction" might provide a novel method to regulate the catalytic sites of MoS2 .